Casticin: A natural flavonoid with promising pharmacological and biological activities - Shehroz Abbas; Muhammad Shahbaz; Amjad Ali; Saqlain Irshad; Salman Ahmad; Jaya Seelan Sathiya Seelan; Christophe Wiart; Praneetha Palasuberniam; Nazirah Mustaffa (Elsevier Inc, 2025)
Casticin, a flavonoid extracted from diverse botanical sources, has garnered substantial scientific interest due to its remarkable pharmacological properties and significant therapeutic potential. This review provides an extensive evaluation of casticin’s biological activities, emphasizing its broad-spectrum antimicrobial effects, including antibacterial, antiviral and antifungal. Its anticancer potential is demonstrated by its ability to suppress tumor proliferation, induce apoptosis, and regulate oncogenic pathways. Casticin also exhibits significant antidiabetic properties through enhanced glucose metabolism and insulin sensitivity, along immunomodulatory capacities that modulate cytokine expression and immune cell function. Additional properties include its antioxidant activity, anti-inflammatory effects, and wound-healing potential, characterized by enhanced tissue regeneration and angiogenic. Moreover, the review highlights casticins organ-protective potential, i.e., neuro- protective, cardioprotective, hepatoprotective, nephroprotective, pulmonary, and testicular cryoprotection. The molecular mechanisms underlying these pleiotropic effects have been discussed, particularly its ability to modulate critical signaling pathways and gene expression dynamics. Casticin’s bioavailability, pharma Coki and synergistic potential with other therapeutics further support its promise as a multi-targeted natural compound. This review underscores casticins broad pharmacological spectrum and encourages future research into its clinical applications.